Long‐range transport across the Atlantic in summertime does not enhance the hygroscopicity of African mineral dust. Issue 18 (30th September 2015) - Denjean, C.; Caquineau, S.; Desboeufs, K.; Laurent, B.; Maille, M.; Quiñones Rosado, M.; Vallejo, P.; Mayol‐Bracero, O. L.; Formenti, P.
Abstract We present the first direct evidence that the hygroscopic properties of super micron (>1 µm) African dust particles did not change despite undergoing long‐range transport across the Atlantic toward the Caribbean. Concurrent measurements of chemical composition show that most of mineral dust was chemically unprocessed and externally mixed. A minor portion of mineral dust was internally mixed with sulfate and chloride (~13–24% by number) or aggregated with sea‐salt particles (~3–6%). Only dust particles aggregated with sea salt showed significant hygroscopic growth above 75% relative humidity (RH), resulting in a decrease in extinction mass efficiency by up to a factor 2.2. All other dust particles did not take up significant amounts of water when exposed to up to 94% RH. These results demonstrate that the direct radiative effect of African dust in this region remained independent of RH and an external mixing state could be considered for evaluating the climate effects of dust.